Malformations of the brain in two fetuses with a compound heterozygosity for two PAX6 mutations - Schmidt-Sidor, Bogna; Szymańska, Krystyna; Williamson, Kathleen; van Heyningen, Veronica; Roszkowski, Tomasz; Wierzba-Bobrowicz, Teresa; Zaremba, Jacek (Folia Neuropathologica, 2009)
PPAX6 is an important transcription factor which plays an essential role in brain morphogenesis and eye development. It is related to migration of neuroblasts to the cerebral cortex and deep telencephalic nuclei, and the specification of cellular and regional identity. Disturbances of brain development in two sib fetuses whose parents were aniridic (both sporadic cases) are reported. Molecular analysis in both parents has shown different mutations in PAX6 gene and a compound heterozygosity for two PAX6 mutations in both fetuses. Neuropathologically both cases showed severe brain malformations with increased germinal proliferation, gross disturbances of migration and organization of the CNS.